2020
DOI: 10.1021/acsami.9b22284
|View full text |Cite
|
Sign up to set email alerts
|

Wettability-Engineered Meshes for Gas Microvolume Precision Handling in Liquids

Abstract: The interaction of rising gas bubbles with submerged air-repelling or air-attracting surfaces is relevant to various technological applications that rely on gas-microvolume handling or removal. This work demonstrates how submerged metal meshes with super air-attracting/repelling properties can be employed to manipulate microvolumes of air, rising buoyantly in the form of bubbles in water. Superaerophobic meshes are observed to selectively allow the passage of air bubbles depending on the mesh pore size, the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Over time, developments in surface engineering techniques have facilitated the manipulation of different liquids on wettable and nonwettable surfaces. In particular, different spreading behavior of liquids on wettable and nonwettable surfaces has demonstrated a variety of interesting phenomena by confining and transporting liquid volumes passively via spatially juxtaposed wettable and nonwettable regions, partitioned by sharp wettability contrast lines. In the past two decades, applications of such surfaces have become increasingly popular in different areas, such as electronic cooling, condensation heat transfer, , open-surface microfluidics, and air bubble manipulation underwater. , …”
Section: Introductionmentioning
confidence: 99%
“…Over time, developments in surface engineering techniques have facilitated the manipulation of different liquids on wettable and nonwettable surfaces. In particular, different spreading behavior of liquids on wettable and nonwettable surfaces has demonstrated a variety of interesting phenomena by confining and transporting liquid volumes passively via spatially juxtaposed wettable and nonwettable regions, partitioned by sharp wettability contrast lines. In the past two decades, applications of such surfaces have become increasingly popular in different areas, such as electronic cooling, condensation heat transfer, , open-surface microfluidics, and air bubble manipulation underwater. , …”
Section: Introductionmentioning
confidence: 99%
“…Surface wettability is generally characterized by the equilibrium contact angle (CA) of a sessile droplet on the surface in air. The superhydrophilic (SHI) surface in air (CA < 10°) becomes superaerophobic under water and vice versa for the superhydrophobic (SHO) surface (CA > 150°). , Air bubble manipulation in a submerged state has been investigated both using active and passive methods related to surface wetting properties. For example, bubble movement on the superwetted surface covered by special lubricant (ferrofluid or paraffin) under the stimulus of the magnetic field or light is investigated for the bubble intentional control. , In addition, some surfaces doped with magnetic particles are used to manipulate bubble motion under the stimulus of the magnetic field .…”
Section: Introductionmentioning
confidence: 99%
“…For example, bubble movement on the superwetted surface covered by special lubricant (ferrofluid or paraffin) under the stimulus of the magnetic field or light is investigated for the bubble intentional control. , In addition, some surfaces doped with magnetic particles are used to manipulate bubble motion under the stimulus of the magnetic field . Most of passive methods are based on surface wettability patterns such as wedge-shaped channel, constant-width channel, Janus surface, cone, , wettability gradient surfaces, , and dual rails . The surfaces were mainly fabricated by chemical etching ,, and laser milling. , ,,, The pumpless air bubble spreading is driven by the force arising from the asymmetric channel geometry or wettability gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement of surface engineering techniques has facilitated scalable approaches for fabricating wettable and nonwettable surfaces, on which a variety of liquids can be manipulated. Distinctly different behaviors of fluids encountering wettable and nonwettable surfaces enable effective confinement of liquid volumes on surfaces possessing spatially juxtaposed wettable and nonwettable domains separated by a sharp wettability-contrast line. The scientific literature from the last two decades bears testimony to the applicability of wettability-patterned surfaces in open-surface microfluidics, pool boiling, condensation, , and electronics cooling. , A superhydrophobic (water-repelling) surface behaves as a superaerophilic (air-attracting) one when submerged in water, and vice versa for a superhydrophilic surface. , A review of the various fabrication techniques for obtaining superaerophobic and superaerophilic surfaces was recently presented by George et al Numerous studies have shown possible applications of such surfaces in gas harvesting, wastewater remediation, catalytic action, drag reduction, etc.…”
Section: Introductionmentioning
confidence: 99%